Ethnoracial and rural-urban differences in female sterilization in Bolivia, Colombia, Guatemala, and Peru - Mena-Meléndez, Lucrecia (Frontiers in Global Women's Health, 2025)
IntroductionIn Latin America, 26 percent of women use sterilization to avert unwanted pregnancies. Although sterilization provides first-tier effectiveness, long-acting continuation over time, and life-long cost-benefit, previous research has documented persistent inequalities in access and use worldwide.MethodsThis study uses Demographic and Health Survey (DHS) data for Bolivia, Colombia, Guatemala, and Peru (1986-2015), to explore ethnoracial, geographic, socioeconomic, individual, and reproductive differences in female sterilization [N (level-1 women) = 112,135; N (level-2 clusters) = 4,946].ResultsResults from descriptive analyses and logistic multilevel regression models indicate that ethnoracial minorities and rural women had lower odds of reporting female sterilization as their current contraceptive method. Compared to Bolivian women, Colombian and Guatemalan women had higher odds of reporting sterilization, while Peruvian women had lower odds. Older, wealthier, more educated, and those employed outside the home had higher odds of reporting sterilization. Additionally, those older at first birth, with higher parity, with a longer interval since preceding birth, and with previous experience with unintended pregnancies had higher odds of reporting sterilization.DiscussionFindings suggest that social, geographic, and structural factors may shape equitable access to sterilization for some groups. Future efforts should prioritize reducing access gaps between ethnoracial groups and rural-urban populations by strengthening health systems and ensuring culturally appropriate, equitable care.